Student sports achievement: Can it control body mass index (BMI) and cholesterol? - Wati, Isti Dwi Puspita; Kusnanik, Nining Widyah; Wahjuni , Endang Sri; Samodra, Y Touvan Juni; Sastaman B, Putra; Suryadi, Didi (SPORT TK-EuroAmerican Journal of Sport Sciences, 2024)
The aim of this study was to assess the BMI and cholesterol levels of athletes selected for preparation for the National Sports Week in Indonesia. The study used a quantitative approach through a survey with researchers giving a test and measurement. The subjects used as research samples were all athletes in the sports of Weightlifting, Fencing, Aero Modeling, Bicycle Racing, Billiard, Handball, Badminton, Parachuting, Judo, Karate, Kempo, Muay Thai, Archery, Wall Climbing, Pencak Silat, Petangque, Swimming, Sepak Takraw, Taekwondo, Tarung Derajat, Table Tennis, Boxing, Volly Beach, Wushu. Additionally, following the selection test, a total of 328 athletes were included in the study. Instruments utilized in this study included the Omron Karada Scan HBF-328 scales for weight measurement, and the OneTouch device for cholesterol testing. The data were analyzed using Microsoft Excel and IBM SPSS Statistics version 26. The results revealed that the mean BMI and cholesterol levels were 22.85 and 171.38, respectively. Among the athletes, 11% were categorized as underweight, 63.11% as normal weight, 21.65% as overweight, 2.74% as obese I, 0.91% as obese II, and 0.61% as obese III. In terms of cholesterol levels, 80% were within the normal range, 10% were low, and 10% were high. Non-parametric correlation analysis demonstrated no significant relationship between BMI and cholesterol levels among the athletes, with a significance value of 0.815. This study concluded that the athlete's BMI was normal, as well as the average athlete's cholesterol condition in normal conditions.